2018
DOI: 10.1007/s11071-018-4641-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of hysteretic stiffness related effects in contact-type nonlinearity

Abstract: The paper presents experimental works related to contact nonlinearities. The research is focused on effects derived from hysteresis stiffness characteristics and vibro-impacts generated during the relative movement of two surfaces. The modeling of the contact nonlinearities was divided in two parts. First, the parameters of the system were identified based on modal analysis test. Next, the model was created and verified with experimental data. The experimental works were performed on steel samples with prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…However, it has been proved that the nonlinear techniques such as signal modulation [1], shift of resonance frequency [2] (e.g. nonlinear resonant ultrasound spectroscopy), sub-and higher harmonic generation [3], frequency mixing [4], modulation transfer (Luxembourg-Gorky effect) [5] and many others [6] are sensitive enough to observe any changes in structural integrity. As in the case of the whole monitoring system, the structure itself can exhibit multiple nonlinear sources, such as the material nonlinearity (usually exhibited through plasticity changes or thermal aging) [7], the cumulative presence of pores in freshly manufactured materials [8], delamination, de-bonding among the layers of the structure [8], the adhesive layer or debonding between the structure and transducer [9], and finally, the nonlinear movement of the cracks surfaces (breathing [10], micro-slip [11] or stick-and-slip [12]).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been proved that the nonlinear techniques such as signal modulation [1], shift of resonance frequency [2] (e.g. nonlinear resonant ultrasound spectroscopy), sub-and higher harmonic generation [3], frequency mixing [4], modulation transfer (Luxembourg-Gorky effect) [5] and many others [6] are sensitive enough to observe any changes in structural integrity. As in the case of the whole monitoring system, the structure itself can exhibit multiple nonlinear sources, such as the material nonlinearity (usually exhibited through plasticity changes or thermal aging) [7], the cumulative presence of pores in freshly manufactured materials [8], delamination, de-bonding among the layers of the structure [8], the adhesive layer or debonding between the structure and transducer [9], and finally, the nonlinear movement of the cracks surfaces (breathing [10], micro-slip [11] or stick-and-slip [12]).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it can be described by high-order elastic constants or nonlinear ultrasonic coefficients [24]. The contact nonlinearity of solids mainly comes from the nonlinear stressstrain of cracks, interfaces, and contact surfaces [25,26], which reflects the local defect characteristics of materials. The existence of defects will lead to strong nonlinear distortion when ultrasonic interacts with it.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the authors focused on the symmetric hysteretic model presented by Solodov et al [26], which after the experimental analysis was modified to an asymmetric hysteretic model. The choice was based on the findings presented by Klepka et al [10], where the hysteretic motion between two surfaces was shown via experimental investigation. Furthermore, the time periods of the stick and slip motions were pointed out in the displacement and velocity responses of the analyzed system.…”
Section: Introductionmentioning
confidence: 99%